War at sea: Portugal, navigation and maritime commerce during World War One - Miguel Castro Brand\~ao (Essays in Economic & Business History (EEBH), 2021)
This article presents new research on the Portuguese Maritime Front during World War One, especially regarding the German submarine war off the Portuguese coast. One subject, in particular, has remained obscure for many contemporary Portuguese historians: the direct and indirect impacts of the German submarine war on the Portuguese economy. In this article, we correlate the material losses provoked by German submarines in the Portuguese Atlantic with fluctuations in maritime commerce during the Great War. This approach sheds new light on how the war at sea affected the economies of peripheral countries like Portugal.
Keywords: 330; Portugal; World War One; German Submarine War; Navigation